Protective Effect of Folic Acid against Apoptosis Induced byIschemia/Reperfusion Injury in Rat Liver: Folic acid protective effect - Pronobesh Chattopadhyay; Anjani Sharma; Pallab Chaudhuri; Arun Kumar Wahi (Iranian Journal of Pharmaceutical Sciences, 2007)
The anti-apoptotic gene bcl-2 is located in mitochondria, but it is uncertainwhether its expression affects hepatocyte survival in ischemia/reperfusion (I/R) injury.This experiment was designed to evaluate the role of folic acid in expression of bcl-2in I/R in rat liver. Eighteen Wister rats were divided into sham-operated controlgroup (C) (n=6), I/R group (n=6), folic acid treated group which received 1mg/kg/day folic acid by oral route for 7 days before induction of I/R (n=6). Bcl-2expression was measured by RT-PCR and western blot methods. Folic acidsignificantly increased Bcl-2 mRNAexpression in comparison to the I/R group.Quantification of apoptotic and necrotic hepatocytes, measured by fluorescencemicroscopy and terminal deoxynucleotidyl transferase (TdT)-mediated dUDP-biotin nick end labeling (TUNEL) method, showed a significant decrease inapoptosis and necrosis of hepatocytes in folic acid-treated group. Histopathologi-cal examination of the liver revealed that folic acid protected from severe hepaticdegeneration from I/R injury. The biochemical parameters like alanine transaminasesand aspartate transaminases were significantly decreased in folic acid-treated groupcompared to I/R group. In conclusion, folic acid afforded significant protection againstI/R injury due to its ability to inhibit I/R-induced apoptosis.